PENGEMBANGAN USAHA KEMPLANG BAGI PETANI RAWA LEBAK DI DESA SIMPANG PELABUHAN DALAM KECAMATAN PEMULUTAN KABUPATEN OGAN ILIR - Pusnita, Indah; Ivana, Ivana; Sakir, Icuk Muhammad; Izdihar, Ahmad Ariq; Anggraini, Nabila Dhea (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2026)
Swamp farmers in Simpang Pelabuhan Village, Pemulutan District, Ogan Ilir Regency, have economic potential through processing fish into kemplang. However, their kemplang business still faces various obstacles, such as limited production technology, simple business management, inconsistent product quality, and limited marketing reach. This community service activity aims to develop the kemplang business of swamp farmers by increasing production capacity, business management, and marketing. The methods used include training in hygienic and high-quality kemplang processing, mentoring in business management and simple financial records, providing production equipment, and strengthening marketing strategies. The results of the activity show an increase in partners' skills in the kemplang production process, improvements in product quality and quantity, and an increase in partners' understanding of sustainable business management. Thus, this activity contributes to increasing the income and welfare of swamp farmers through the development of a kemplang business based on local potential.